Parámetros de crecimiento individual de Petrolisthes caribensis (Werding, 1983) y Petrolisthes galathinus (Bosc, 1902) (Decapoda: Porcellanidae) en el golfo de Morrosquillo, Caribe colombiano (2014)
ABSTRACT: To determine if there was variation in growth parameters between two ecologically and phylogenetically related species, the ELEFAN I application was used (FISAT II FAO-ICLARM). Based on an eleven months of sampling, the asymptotic length (L ∞) and growth constant (K) were estimated from size distributions of two species of crustaceans, Petrolisthes caribensis and Petrolisthes galathinus. The samples were obtained with artificial collectors located on a rocky shore zone in the northern portion fo the Gulf of Morrosquillo, San Onofre (Sucre), Colombia. The results showed that the K value of the three morphotypes of P. galathinus ranged from 2.2 to 2.9, and the L∞ ranged from 10.6 to 12.15 mm. In P. caribensis (Blue), K ranged from 2.4 to 2.7, and the L∞ from 11.8 to 12.2 mm. The von Bertalanffy growth coefficient and the maximum sizes of all females of the morphotypes of the two species were lower than in males, which could be related to territorial defense in males and to reproductive energy investment in the case of females. The coefficient of variation of the phi prime index (Ø’) among species and sexes was less than 4%, which indicates that were are no differences between growth parameters within species, probably due to a phylogenetic restriction. In general, the benthic phase of the life cycle of these two species of porcellanids, from megalope stage to adult, lasted from between 39 and 45 days.